1998
DOI: 10.1006/viro.1998.9207
|View full text |Cite
|
Sign up to set email alerts
|

Three Closely Related Herpesviruses Are Associated with Fibropapillomatosis in Marine Turtles

Abstract: Green turtle fibropapillomatosis is a neoplastic disease of increasingly significant threat to the survivability of this species. Degenerate PCR primers that target highly conserved regions of genes encoding herpesvirus DNA polymerases were used to amplify a DNA sequence from fibropapillomas and fibromas from Hawaiian and Florida green turtles. All of the tumors tested (n = 23) were found to harbor viral DNA, whereas no viral DNA was detected in skin biopsies from tumor-negative turtles. The tissue distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
133
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 12 publications
13
133
1
5
Order By: Relevance
“…But the nucleotide sequences showed little homogeneity when compared with DNA databases using a BLAST2.0.7 program [1]. The nucleotide sequences obtained in the present study also showed only 57% homogeneity with those reported in the cases of green turtle fibropapillomatosis [10]. This fact suggests that the sequence determined in the present study may be ascribed to a new type of tortoise herpesviral DNA, which most likely belongs to the alpha subfamilies of herpesviridae [11], judging from its amino acid sequence.…”
contrasting
confidence: 71%
See 3 more Smart Citations
“…But the nucleotide sequences showed little homogeneity when compared with DNA databases using a BLAST2.0.7 program [1]. The nucleotide sequences obtained in the present study also showed only 57% homogeneity with those reported in the cases of green turtle fibropapillomatosis [10]. This fact suggests that the sequence determined in the present study may be ascribed to a new type of tortoise herpesviral DNA, which most likely belongs to the alpha subfamilies of herpesviridae [11], judging from its amino acid sequence.…”
contrasting
confidence: 71%
“…In the present study, analysis of the nucleotide sequence of the tortoise herpesviral DNA showed that the 230-bp sequence obtained in our study differed from that in a herpesvirus found in green turtle fibropapillomatosis [10], suggesting the possibility of a new type of tortoise herpesviral DNA, most likely belonging to the alpha subfamilies of herpesviridae [11], as mentioned above. The PCR method using a consensus primer may thus be another useful method for identifying herpesviral infections in tortoises, and especially effective in the diagnosis of early or latent infections in living tortoises.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The disease, which disrupts the daily activities of affected animals, is characterized by the formation of lobulated fibrous tumors, frequently around the neck, eye, mouth, flipper and/or oral cavity, and occasionally within visceral organs, such as lung, kidney, and heart. Recent studies have implicated viruses, notably a herpesvirus and retrovirus, as the potential cause of green turtle fibropapilloma (GTFP) (1,6,13,25). However, to date, no virus has been isolated in cell culture, and the pathogenetic role of herpesviruses or retroviruses has not been established (11).…”
Section: Introductionmentioning
confidence: 99%